The Impact of Mass Media on Political Support A Preferences-Perceptions Model of Media Effects (Volume 1) - Floß, Daniela (Nomos Verlagsgesellschaft mbH & Co. KG, 2010)
Why is citizens' support for political actors and institutions declining? Recent research suggests that voter cynicism is fueled by the manner in which mass media covers political events and issues. This dissertation provides evidence regarding the impact that media coverage of political decision-making procedures has on an audience's political support. It focuses on the role of individual expectations and preferences of the audience. Empirically-standardized online surveys, an experimental study, and a comprehensive content analysis of news coverage were conducted for this study. It shows that mass media may contribute to a decrease of political support by shaping the perception of political processes. In addition, the findings suggest that the media's impact on political support was particularly strong if media coverage shapes the impression that political processes do not match individual preferences. This book contributes to a differentiation of the rather general claim that negative or critical media information results in a decline of political support.